Sulfamide‐Lattice Restructuring To Form Dimensionally Controlled Molecular Arrays and Gel‐Forming Systems. Issue 15 (9th February 2017) - Raghava, Saripalli V.; Gopinath, Pushparathinam; Srivastava, Bhartendu K.; Ramkumar, Venkatachalam; Muraleedharan, Kannoth M.
Abstract: A design approach that incorporates structural requirements for the formation of a 1D assembly, fibril stability, and fibril–fibril interactions for gelation was attempted by using amino acid‐based sulfamides with the general structure Aa‐NH‐SO2 ‐NH‐Aa (Aa=amino acid). A preference for 1D assembly alone was not a sufficient condition for gelation, which became evident from studies involving sulfamide esters 1 –5 . Reducing the crystallization tendency without hindering unidirectional growth was executed through diacids of the sulfamide precursors with various amines that form an envelope around the sulfamide core through salt bridges. This strategy was fruitful, and gels of a wide variety of solvents could be formed by varying the acid and amine components. The use of dodecylamine or benzylamine, which could stabilize the molecular layers through alkyl‐chain segregation or π–π interactions improved the gelation tendency, whereas the nature of the amino acid side chain, especially the rotational freedom and hydrophobicity, had a direct role in dictating the solvent preference. Crystallographic studies of these two‐component systems gave molecular‐level insight into the assembly and showed the importance of anisotropy in the distribution of secondary interactions in gelation. Abstract : A rational gel design approach incorporates structural requirements for the formation of a one‐dimensional assembly, fibril stability, and fibril–fibril interactions by using amino acid‐based sulfamides with various amines (see figure). An extended assembly, directed by a sulfamide core with a hydrophobic periphery provided by the amine component, proved very effective in the gelation of a wide variety of solvents.